Diets, Food Choices and Environmental Impacts across an Urban-Rural Interface in Northern Vietnam - Trinh, H.T.; Linderhof, V.; Vuong, V.T.; Esaryk, E.E.; Heller, M.; Dijkxhoorn, Y.; Nguyen, T.M.; Huynh, T.T.T.; Duong, T.T.; Luu, V.T.; Jones, A.D.; Talsma, Elise F.; et al. (MDPI, 2021)
Human diets and their associated environmental impacts differ across segments of the population. There is evidence that consumer choices of food intake can also affect the overall environmental impacts of a food system. This paper analyzes the environmental impact of diets and food choices across a rural–urban transect in Northern Vietnam by using mixed survey data from 619 adult respondents. The average greenhouse gas emissions (GHGE) resulting from producing the daily food intake of adults in the urban and peri-urban districts were similar, while the average in the rural district was lower. Although starchy staples contributed the most to energy intake, pork and beef were the largest contributors to GHGE. Metrics of blue water use were higher for diets of males than those of females in all three districts. Interestingly, the difference in mean diet diversity score between urban and rural households was significant, and females’ diets were more diverse than those of males. As expected, urban households were more likely to buy food, while rural households often produced their own foods. Urban households reported prioritizing personal health and the natural content of food and would increase seafood and fruits if their income were to increase. In rural regions, interventions aimed at reducing undernutrition should address improving diet quality without significant increases to diet-related environmental impacts.